Inside the Black Box of Improving on Nursing Home Quality Measures. (December 2021) - Davila, Heather; Shippee, Tetyana P.; Park, Young Shin; Brauner, Daniel; Werner, Rachel M.; Konetzka, R. Tamara
Nursing Home Compare (NHC) reports quality measures (QMs) for nursing homes (NHs) as part of its 5-star rating system. Most of the QMs are based on facility self-reported data, prompting questions about their validity. To better understand how NHs interact with the QMs, we used qualitative methods, including semistructured interviews with NH personnel ( n = 110), NH provider association representatives ( n = 23), and observations of organizational processes in 12 NHs in three states. We found that most NHs are working to improve the quality of care they provide, not merely their QM scores. However, our interviews and observations revealed limitations with the QMs, suggesting that the QMs—on their own—may not accurately reflect the quality of care NHs provide. Our findings suggest several changes to improve NHC, including adding information related to resident and family experience, providing greater risk adjustment, and providing incentives for NHs that serve socially and medically complex residents.